Eight Bits PCM Speech Coder And Decoder - Ibrahim, Imee Ezainee (Universiti Sains Malaysia, 2006)
The scope of this project is divided into three main parts. Part one involves to study and understand the operation of an eight bit PCM Coder and Decoder that used for speech coding. The second part is to study the architecture of TMS320C6416 DSP Processor. The third part is to implement the PCM Coder and Decoder in real time using the TMS320C6416 DSP Processor. The study of the PCM Coder and Decoder has been carried out by considering a three bit PCM system and its simulation is done by using MATLAB and Simulink. Finally, the eight bit PCM Speech Coder and Decoder was implemented in real time by using the TMS320C6416.